KONTRIBUSI KEGIATAN EKSTRAKURIKULER PRAMUKA UNTUK PENGUATAN MENTAL DAN KETERAMPILAN PESERTA DIDIK - Ridwan Ridwan (QATHRUNÂ, 2019)
The objectives of this study were to: 1) describe the Contribution of Scout Extracurricular Activities to Mental Strengthening Students at SMKN 1 Anyer; 2) Scout Extracurricular Contribution to Students' Skills Improvement; 3) explain the Constraints for the coaches and trainers on extracurricular activities at SMKN 1 Anyer. This research method is descriptive qualitative, namely research that attempts to describe a symptom, event, event that is happening now. The data for the three variables were obtained through interviews, observation, and document checking. The research sites are SMK Negeri 1 Anyer which is located on Jalan Raya Anyer-Mancak Km 02, Grogol Indah Village, Anyar District, Serang Regency and Al-Khairiyah 1 Cilegon High School which is located on Jalan Sunan Bonang, Kubangsari, Ciwandan District, Cilegon City, Banten Province, while The research took place from 10 July 2019 to 10 January 2020. Respondents taken by the researcher were 2 school principals, 2 deputy school principals, 2 scout coaches, 3 trainers, homeroom teachers, PKN teachers, PAI teachers, BP / BK teachers, and several students who actively participated in the scout movement extracurricular activities, totaling 78 students. The results of the research on extracurricular activities contribute to mental strengthening, especially spiritual, emotional, and social aspects; 2) extracurricular activities contribute to improving skills, especially managerial, physical, and knowing nature; 3) Obstacles in scout extracurricular activities at SMA Negeri Anyer, namely the limited number of coaches in both numbers and abilities; low interest in students; lack of parental support.